A new admission method may select applicants with a distinct personality profile. (3rd June 2017) - Talmor, Aya G.; Falk, Amir; Almog, Yaniv
Abstract: Background: There is little data to suggest that a specific admission method can select students with a distinct personality profile. We have recently introduced a new admission process that combines a computerized personality test, with a single interview. The purpose of the current study was to find whether the new method selects applicants with a different personality profile and attitudes compared with the previous method. Method: Using a validated personality questionnaire (HEXACO) and attitudes questionnair, that were filled anonymously between November 2014 and May 2015, the authors compared two groups of students: group A comprising students accepted with the new method (first and second year) with group B comprising students accepted with the previous method (third to sixth year). Results: In group A, 157 responded out of 250 (63%), while in group B 194 out of 352 (55%). Group A students ranked significantly higher in honesty-humility, extraversion, agreeableness and openness to experience, and lower in emotionality. Physicians' role in society was perceived to be more meaningful among Group A students ( M = 4.19, SD = 0.50, N = 152) compared to Group B students ( M = 3.86, SD = 0.57, N = 184). Conclusions: The new method may select applicants with a distinct personality profile and different attitudes toward the physicians' role in the society.